Energy Performance of the European Union Countries in Terms of Reaching the European Energy Union Objectives - Roman Vavrek (Energies, 2020)
European energy policy, especially the project of the Energy Union, is one of the most rapidly developing areas of the EU, and one through which European institutions are obtaining gradually more extensive power over the performance of the national energy sectors. The paper focuses on an analysis of the energy performance of EU member states (MS) with regard to the priorities of the European Energy Union. For an assessment of the energy performance of EU countries, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) was chosen, using the Coefficient of Variation method (CV) as an objective method for determining the weights of eight input indicators, including CO2 intensity, electricity and gas price, energy productivity, energy dependence, consumption of renewables and research and development. The analysis for the period from 2008 to 2016 showed significant changes in the input indicators, which directly influenced the results of both methods mentioned above. Long-term differences between the best- and worst-rated countries are seen mainly in CO2 emissions, energy imports and total consumption of renewable energy sources. It is these aspects of comprehensive energy performance and their convergence at the level of EU countries that we believe should be addressed in the near future.